Sustainable Farming: A Political Geography - Paarlberg, Robert L. (International Food Policy Research Institute, 1994)
Farming is a threat to the natural environment in rich as well as poor countries, but the human stakes are now much higher in the developing world, where food needs are acute and growing rapidly. Roughly 700 million people in developing countries do not have access to sufficient food supplies to meet their needs for a healthy and productive life. Already because of population growth, the developing world is being asked to feed 88 million additional people every year. How can this production task be met if environmentally destructive farming practices continue? Paarlberg examines the geography and the politics of resource abuse. He concludes that the sustainable farming debate will remain deadlocked until it is recast in a region-specific and politically aware form that emphasizes the vastly different circumstances of farmers in different parts of Asia, Africa, and Latin America. If regional precision is maintained, paralyzing technical arguments between powerful agriculturalists and environmentalists can be minimized, and important reform imperatives that go beyond technical choice can be highlighted as well.